Effects of doxycycline on clinical, microbiological and immunological parameters in well‐controlled diabetes type‐2 patients with periodontal disease: a randomized, controlled clinical trial. (3rd September 2014) - Tsalikis, Lazaros; Sakellari, Dimitra; Dagalis, Panagiotis; Boura, Panagiota; Konstantinidis, Antonios
Abstract Aim To evaluate the clinical, microbiological and immunological effects of systemic doxycycline as an adjunct to scaling and root planing (SRP) in chronic periodontitis patients with well‐controlled type 2 diabetes. Materials and Methods Sixty‐six patients compliant to oral hygiene (Hygiene Index <20%) allocated to either a test (systemic doxycycline for 21 days) or a control (placebo) group participated in the present randomized controlled trial (RCT). Clinical assessments were recorded at baseline, 3 and 6 months after therapy and included clinical attachment level (CAL), set as the primary outcome of the study, probing pocket depth (PPD), recession (RE) and bleeding on probing (BOP). At the same time points, counts of 15 subgingival species were evaluated by "checkerboard" DNA‐DNA hybridization, gingival crevicular fluid samples were analysed for matrix metalloproteinase‐8 (MMP‐8) by ELISA and HbA1c levels were determined. Comparisons between and within groups were performed by non‐parametric tests (Mann–Whitney, Wilcoxon signed‐ranks and z‐test for proportions with Bonferroni corrections) at the 0.05 level. Results No major differences were noticed in clinical and microbiological parameters of periodontal disease or levels of MMP‐8 between the two groups. Conclusions Adjunctive systemic doxycycline does not seem to significantly enhance the effects of SRP in well‐controlled diabetes type 2 patients.